Kaingáng : uma história das interações entre nativos e ocidentais durante a conquista e a colonização no sul do Planalto Meridional - Francisco, Aline Ramos (2013)
This research analyzes the articulated social interactions by kaingáng from the Iberian conquest. A diversity of interactions between native and new residents, including situations of servitude, slavery, protection and integration and alliances. There is the link between occupation, colonization and seizure expeditions that had intended to release areas for colonization. The captivity and/or servitude of indigenous minors were part of this historical context. At the same time, we reviewed the situations in which the Western or native aprisionavam kaingáng, as part of its social organization, as well as the transformations and rearticulations. There were friendly interactions during the period, through informal alliances with local farmers or through the village's formality. The insertion/subordination of kaingáng implied the pursuit of power and prestige among the kaingáng by establishing formal relations with the Government in the context of conflicty.